Using Ulcerative Colitis As A Basis For Modern Diagnosis (Eurasian Medical Research Periodical, 2025)
The significance of ulcerative colitis diagnosis in conventional medicine, the many contemporary diagnoses of orcalous ulcerative colitis, the scope of the diagnostic using index and scale, and the established diagnosis of tugri are all discussed in this article